Strategic Health Communication and Digital Business Transformation in the Halal Supplement Industry: Evidence from an Indonesian SME - Rendi Rendi; Yulianto Yulianto; Yoyo Hambali; Wantoro Wantoro; M. Ali Murtado; Mawarni Mawarni (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2026)
The global halal pharmaceutical and health supplement industry is experiencing rapid digital transformation, requiring companies to develop not only product competitiveness but also strategic communication capabilities capable of strengthening consumer trust and health literacy. This study aims to analyse the strategic positioning and business development strategy of PT VitaBrain Indonesia, a halal brain health supplement company producing Centella asiatica-based products, through the integration of SWOT analysis, the Internal-External (IE) Matrix, and strategic health communication perspectives. This study employed a qualitative-dominant mixed-methods case study approach using semi-structured interviews, digital observations, and source triangulation involving company management, distributor agents, and loyal consumers. Internal and external strategic factors were analysed using IFAS–EFAS matrices, IE Matrix positioning, and TOWS strategic formulation. The findings indicate that PT VitaBrain Indonesia is positioned within Quadrant V (“Hold and Maintain”) with an IFAS score of 2.71 and an EFAS score of 2.57. The study reveals that the company’s primary challenge does not originate from product legitimacy or quality limitations, but rather from insufficient digital communication capability, declining conventional distribution effectiveness, and increasing digital misinformation threats. The results further demonstrate that strategic health communication functions as a critical organizational capability capable of strengthening health literacy, digital trust, consumer engagement, and sustainable competitiveness within digital halal healthcare markets. Theoretically, this study contributes to the strategic management and health communication literature by extending the Resource-Based View (RBV) and Health Belief Model (HBM) into the context of halal digital healthcare SMEs. The study proposes that strategic health communication should be conceptualized as an intangible strategic asset capable of supporting sustainable business transformation within highly competitive digital marketplaces.